Estudo sobre a qualidade das casas construídas pelo Projeto EcoLar e seu impacto como construção de interesse social sustentável - Vasques, Timóteo de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This paper consists of an analysis of the quality of the houses built by the social startup Mangalô (www.mangalo.org.br), which in 2014 created the EcoLar Project, a private initiative of Sustainable Social Interest, aimed at the construction of modular houses, called EcoLares, for families in situations of social vulnerability in the Rodoanel community, in the region of Parque São Rafael, in São Paulo-SP. EcoLares are built in a short time, using recycled and recyclable materials and voluntary labor. An EcoLar usually takes one to two days (a weekend) to be build. The analyzes presented were based on the monitoring of the construction process of several EcoLares, technical visits to existing EcoLares and the application of a questionnaire to families benefited by the Project. Based on the improvement opportunities observed in all these stages, a study was proposed and presented to those responsible for the Project, suggesting the structuring of a Quality Management System for application in the execution of future EcoLares. A comparative study was also carried out between the costs of building an EcoLar with improvements already implemented and those of a conventional masonry construction for the same size. The studied and applied solutions brought clear results, showing that it is advantageous for the Project to pursue the path of quality, that will assure a considerable improvement in the delivery of the final product and maybe attract attention and investors, which will allow the production of more EcoLares for benefiting a greater number of families, thus contributing to mitigate the housing deficit in our country, with simple yet dignified, accessible, safe and quality homes for those who need them.

Este trabalho consiste em uma análise da qualidade das casas construídas pela startup social Mangalô (www.mangalo.org.br), que em 2014 criou o Projeto EcoLar, iniciativa privada de Habitação de Interesse Social Sustentável voltada para a construção de casas modulares, denominadas EcoLares, para famílias em situação de vulnerabilidade social na comunidade do Rodoanel, na região do Parque São Rafael em São Paulo- SP. Os EcoLares são construídos em curto espaço de tempo, usando materiais reciclados e recicláveis e mão de obra voluntária. Geralmente um EcoLar leva de um a dois dias (um final de semana) para ser construído. As análises apresentadas ocorreram a partir do acompanhamento do processo de construção de diversos EcoLares, de visitas técnicas a EcoLares existentes e da aplicação de questionário a famílias beneficiadas pelo Projeto. A partir das oportunidades de melhoria observadas em todas essas etapas, foi proposto e apresentado aos responsáveis pelo Projeto, um estudo sugerindo a estruturação de um Sistema de Gestão da Qualidade para aplicação na execução de futuros EcoLares. Também foi realizado um estudo comparativo entre os custos de construção de um EcoLar, já com melhorias implementadas, e os de uma construção convencional de alvenaria para o mesmo porte. As soluções estudadas e aplicadas trouxeram nítidos resultados, evidenciando ser vantajoso ao Projeto perseguir o caminho da qualidade, que além de garantir uma melhora considerável na entrega do produto final, poderá chamar a atenção e atrair investidores, o que permitirá a viabilização da produção de mais EcoLares, passando a beneficiar um maior número de famílias, contribuindo assim para mitigar o deficit habitacional do nosso país, com moradias simples, porém dignas, acessíveis, seguras e de qualidade para os que delas necessitem.
Study on the quality of houses built by the EcoLar Project and their impact as a construction of sustainable social interest
Keywords: Housing of sustainable social interest; Low cost and sustainable housing; Quality control in construction; Construction quality management; Sustainability; Modular construction; Habitação de interesse social sustentável; Controle da qualidade em obras; Gestão da qualidade de obras; Projeto EcoLar; Sustentabilidade; Construção modular; Gestão da qualidade total; Habitações - projetos e construção